1994
DOI: 10.1007/bf00877926
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral pretreatment with metoprolol on left ventricular wall motion, infarct size, hemodynamics, and regional myocardial blood flow in anesthetized dogs during thrombotic coronary artery occlusion and reperfusion

Abstract: Oral pretreatment with metoprolol limited infarct size and improved regional left ventricular function, probably due to its negative chronotropic and inotropic effects, and also due to an enhancement of collateral flow fr

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Although TTC staining to discriminate between VIT and NIT may require a certain period of reperfusion [37], it does allow for sensitive and specific determination of infarct size [38]. We and other authors have previously shown the validity of TTC staining in this and other models [18,39,40]. Isoflurane is known to have a protective effect in terms of preconditioning [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although TTC staining to discriminate between VIT and NIT may require a certain period of reperfusion [37], it does allow for sensitive and specific determination of infarct size [38]. We and other authors have previously shown the validity of TTC staining in this and other models [18,39,40]. Isoflurane is known to have a protective effect in terms of preconditioning [25].…”
Section: Discussionmentioning
confidence: 99%